2022
DOI: 10.56910/jvm.v8i1.188
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Packaging, Promosi Melalui Media Sosial Dan Variasi Produk Terhadap Keputusan Pembelian Konsumen (Studi Kasus Niten Jamu Semarang)

Abstract: Penelitian ini dilakukan di Niten Jamu Kota Semarang yang bertujuan untuk mengetahui pengaruh Packaging, promosi melalui media sosial dan variasi produk terhadap keputusan pembelian konsumen (studi kasus di niten jamu semarang). Data penelitian diperoleh melalui kuesioner dan wawancara. Sampel yang digunakan dalam penelitian sebanyak 60 responden. Hasil penelitian diharapkan dapat memberikan informasi yang berguna bagi para pengusaha maupun pengusaha niten jamu semarang. Data yang diperoleh diolah dengan mengg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
1
1
Order By: Relevance
“…However, the results of this study contradict the findings of previous research conducted by (Herzegovina, 2019) and (Putri et al, 2022), which suggested that product variations have a positive impact on consumer purchasing decisions, both partially and simultaneously.…”
Section: Effect Of Product Variety On Purchase Decisioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the results of this study contradict the findings of previous research conducted by (Herzegovina, 2019) and (Putri et al, 2022), which suggested that product variations have a positive impact on consumer purchasing decisions, both partially and simultaneously.…”
Section: Effect Of Product Variety On Purchase Decisioncontrasting
confidence: 99%
“…These findings align with the research conducted (Luthfiyatillah et al, 2020;Putri et al, 2022;Wintang & Pasharibu, 2021), which similarly demonstrated the positive and significant impact of packaging and social media promotions on consumer purchasing decisions.…”
Section: Effect Of Promotion Media Through Instagram On Purchase Deci...supporting
confidence: 88%
See 1 more Smart Citation